2016
DOI: 10.1007/s10535-016-0627-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of brassinosteroids on ammonium uptake via regulation of ammonium transporter and N-metabolism genes in Arabidopsis

Abstract: Several studies have been performed to elucidate the role of brassinosteroids (BRs) in plant growth and development. However, information on the role of BR signaling in nutrient uptake is limited. This study explores the relationship between BRs and ammonium transporter 1 (AMT1) expression in Arabidopsis roots. We found that BR treatment reduced the expression of AMT1 genes and that a BR receptor BRI1 mutant bri1-5, reversed its BR-repressed expression. Furthermore, the BR signaling transcription factor, BES1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 29 publications
3
26
0
Order By: Relevance
“…Importantly, our study revealed that EPS is the predominant component of 14‐DS‐1 extracts, and DSPS, as its active ingredient, exhibits promising immunoregulatory and anti‐cancer properties. EPSs, which are composed of repeating units of sugars or sugar derivatives, can be grouped into homopolysaccharides or heteropolysaccharides, depending on their monosaccharide compositions . Our analysis revealed that DSPS is a heteropolysaccharide comprising six monosaccharides.…”
Section: Discussionmentioning
confidence: 83%
“…Importantly, our study revealed that EPS is the predominant component of 14‐DS‐1 extracts, and DSPS, as its active ingredient, exhibits promising immunoregulatory and anti‐cancer properties. EPSs, which are composed of repeating units of sugars or sugar derivatives, can be grouped into homopolysaccharides or heteropolysaccharides, depending on their monosaccharide compositions . Our analysis revealed that DSPS is a heteropolysaccharide comprising six monosaccharides.…”
Section: Discussionmentioning
confidence: 83%
“…Similar to the effects of NO in cotton, exogenous hydrogen sulfide production enhances salt tolerance by decreasing Na + content in wheat seedlings . During salt acclimation in Arabidopsis thaliana , cell wall remodeling, ethylene biosynthesis, and signaling pathways play crucial roles . K + and Ca 2+ homeostasis are also important .…”
Section: Salt Stressmentioning
confidence: 96%
“…In cells, mitochondria are the primary source of endogenous intracellular reactive species. These metabolic intermediates play important roles in physiological functions and signaling pathways, both as effectors and as signaling molecules . However, because of the potential toxic impact on key cellular components (e.g.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…These metabolic intermediates play important roles in physiological functions and signaling pathways, both as effectors and as signaling molecules. [58][59][60][61][62] However, because of the potential toxic impact on key cellular Thoracic Cancer 9 (2018) 1575-1582…”
mentioning
confidence: 99%